Uukuniemi virus S RNA segment: ambisense coding strategy, packaging of complementary strands into virions, and homology to members of the genus Phlebovirus. - Simons, J F (1990)
We determined the complete nucleotide sequence of the small (S) RNA segment of Uukuniemi virus, the prototype of the Uukuvirus genus within the Bunyaviridae family. The RNA, which is 1,720 nucleotides long, contains two nonoverlapping open reading frames. The 5' end of one strand (complementary to the viral strand) encodes the nonstructural protein NSs (273 residues; molecular weight, 32,019), whereas the 5' end of the viral-sense strand encodes the nucleocapsid protein N (254 residues; molecular weight, 28,508). Thus, the S RNA uses an ambisense coding strategy previously described for the S segment of two phleboviruses and the arenaviruses. The localization of the N protein within the S RNA sequence was confirmed by amino-terminal sequence analysis of all five possible cyanogen bromide fragments obtained from purified N protein. Northern (RNA) blot analyses with strand-specific probes showed that the N and NSs proteins are translated from subgenomic mRNAs about 800 and 850 nucleotides long, respectively. These mRNAs are apparently transcribed from full-length S RNAs of opposite polarities. The two mRNA species were also detected in virus-infected cells. Interestingly, highly purified virions contained full-length S RNA copies of both polarities at a ratio of about 10:1. In contrast, virions contained exclusively negative-strand copies of the M RNA segment. The possible significance of these results for viral infection is discussed. The amino acid sequence of the N protein showed 35 and 32% homology (identity) with the N protein of Punta Toro and sandfly fever Sicilian viruses, two members of the Phlebovirus genus. The NSs proteins were much less related (about 15% identity). In addition, the extreme 5' and 3' ends of the S RNA, which are complementary to each other, also showed a high degree of conservation with the two phleboviruses. These results indicate that the uukuviruses and phleboviruses are evolutionarily related and suggest that the two genera could be merged into a single genus within the Bunyaviridae family.